Is my body better than yours? Validation of the German version of the Upward and Downward Physical Appearance Comparison Scales in individuals with and without eating disorders - Schönhals, Kristine; Quittkat, Hannah L.; Voges, Mona M.; Ladwig, Gritt; Holtmann, Friederike-Johanna; Vocks, Silja (Frontiers in Psychology, 2024)
Introduction This study examines the psychometric properties of a German version of the Upward and Downward Physical Appearance Comparison Scales (UPACS and DACS). Methods A total of 2,114 participants, consisting of 1,360 women without eating disorders (Mage = 25.73, SDage = 6.84), 304 men without eating disorders (Mage = 24.48, SDage = 6.34), and 450 women with eating disorders (Mage = 27.11, SDage = 7.21), completed the UPACS and DACS as well as further questionnaires on appearance comparisons, eating disorder pathology, and self-esteem. Results Structural equation modeling confirmed the proposed one-factor structure of the original English-language version of the DACS but not of the UPACS. Both scales showed good internal consistency and test–retest reliability. The UPACS and DACS showed the expected correlations with related constructs, indicating acceptable construct validity, with some limitations for women with eating disorders. Discussion Overall, this study indicates that the German versions of the UPACS and DACS are psychometrically suitable for assessing upward and downward physical appearance comparisons in women and men without eating disorders and women with eating disorders in research and clinical practice.